Health Promotion and An Intersectoral Approach in Senior Care Networks - Tatiana Resende Prado Rangel de Oliveira; Cristiane Delesporte Pereira Mattioli; Bárbara Jacome Barcelos; Natália de Cássia Horta; Tatiana Teixeira Barral Lacerda (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: Increase in longevity has caused new demands for health and social development, which in turn points to the need for changes in service structures, health programs, and professional education. OBJECTIVE: To analyze the relation between health promotion in care networks and the intersectorial perspective on senior care. METHODS: This descriptive-exploratory research project was carried out in the Metropolitan Region of Belo Horizonte (RMBH), Minas Gerais, Brazil. Among the 34 cities considered, 10 met the inclusion criteria and took part in the study, i.e. cities with two or more long-stay institutions for seniors (ILPI) in their region. RESULTS: An analysis of interviews enabled the establishment of two categories: "policies and healthcare network for seniors" and "the articulation of health promotion and intersectoriality in senior care." The analyses pointed out differences between the cities with regard to the implementation of national policies and the existence of a guiding document, the difficulty of including seniors in the healthcare network, the decrease in health promotion, and the difficulties and propensities for intersectoriality. CONCLUSIONS: Even though regulation laws for seniors have significantly advanced during the last few years, they were not properly implemented in most of the researched cities. In addition, there is no specific health network for senior care, which is done through Primary Healthcare. With regard to health promotion, actions focused on seniors are specific and isolated, which come from a conceptual reduction of this term.